IMPLICIT MEANING IN FRANZ KAFKA’S NOVEL“METAMORPHOSIS” - Nurul Permata Adinda; Iskandar Iskandar (Faculty of Languages and Literature, Universitas Negeri Makassar, 2021)
This study aims to determine the implicit meaning in Franz Kafka’s novel “Metamorphosis”. The novel talk about the life of Gregor Samsa as the main character. The story began as Gregor transform into a giant vermin and how the situation change in his family after it happened. Gregor Samsa working as a salesman and provide everything to his family. The researcher will use a qualitative method because this study aims to identify the implicit meaning in the novella “Metamorphosis” by Franz Kafka. This research will use an 'descriptive' as the approach that the meaning of events, actions, and expressions is not taken as 'given' or 'self-explanatory', but requires contextual interpretation. The findings in this study reveal that the true meaning in the novel Metamorphosis is a symbol of Kafka's life that describe into Gregor’s life. Gregor failed to conform his needs and his suffering from his mental during the rest of his life. Gregor’s self assessment as a disgusting animal stems from the reality that he stuck and suffer in his human body. The assumsions of Gregor’s life comes because he trapped in his difficult times and failed to be an independent human. It can be conclude that, there are various types of implicit meaning based on every situation, the writer also conclude that there are two main meaning in this nover, the first one is the literal meaning and the second one is the actual meaning.